2015
DOI: 10.1111/jcom.12183
|View full text |Cite
|
Sign up to set email alerts
|

Framing Cancer for Online News: Implications for Popular Perceptions of Cancer

Abstract: News frames can influence how people think about disease. In a pair of studies, we demonstrate how contemporary news outlets frame cancer and how exposure to common frames can affect news audiences' perceptions of those who suffer from cancer. First, we examine the current landscape of frame usage in online cancer news, employing frames ideally suited to the depiction of health and disease. We compare our results with previously published research in this news domain. Second, we employ these frames in a multim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Especially within the context of science communication, the effects of such frames can be profound. Previous studies across a range of science topics have shown that different frames can influence public interest in science issues, perceptions about individuals and diseases (e.g., compassion, stigma), preferences for science-informed policies, as well as personal and political behaviors (Nisbet, 2009;Gallagher and Updegraff, 2012;Gollust et al, 2013;Riles et al, 2015). Some scholars have gone so far as to argue that, in many science debates, power has been determined by one group or individual's ability to define the nature of the problem and to suggest potential solutions-in other words, to frame the issue at hand (Nisbet et al, 2003;Nisbet and Huge, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Especially within the context of science communication, the effects of such frames can be profound. Previous studies across a range of science topics have shown that different frames can influence public interest in science issues, perceptions about individuals and diseases (e.g., compassion, stigma), preferences for science-informed policies, as well as personal and political behaviors (Nisbet, 2009;Gallagher and Updegraff, 2012;Gollust et al, 2013;Riles et al, 2015). Some scholars have gone so far as to argue that, in many science debates, power has been determined by one group or individual's ability to define the nature of the problem and to suggest potential solutions-in other words, to frame the issue at hand (Nisbet et al, 2003;Nisbet and Huge, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Matthew Nisbet (2009) writes, "Scientists can use framing to motivate greater interest and concern thereby expanding the audience for science; to shape preferences for policies informed by or supportive of science; to influence political or personal behavior; to go beyond polarization and unite various publics around common ground; to define policy choices or options; and/or to rally fellow scientists around shared goals or strategy" (57). Indeed, previous studies across a range of science topics have shown that different frames can influence public interest in science issues, perceptions about individuals and diseases (e.g., compassion, stigma), preferences for science-informed policies, as well as personal and political behaviors (Nisbet, 2009;Gallagher and Updegraff, 2012;Gollust et al, 2013;Riles et al, 2015). Some scholars have gone so far as to argue that, in many science debates, power has been determined by one group or individual's ability to define the nature of the problem and to suggest potential solutions-in other words, to frame the issue at hand (Nisbet et al, 2003;Nisbet and Huge, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Framing effects can equally influence how one thinks about people suffering from a disease. In a study by Riles, Sangalang, Hurley, and Tewksbury (2015), the number of stigmatizing thoughts regarding people suffering from cancer was highest when cancer was framed as the consequence of lifestyle choices. When it was framed as being the result of genetic predisposition, however, the number of stigmatizing thoughts was significantly lower.…”
Section: Framing and Stigmamentioning
confidence: 99%